2017
DOI: 10.1111/1753-6405.12547
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular disease risk in young Indigenous Australians: a snapshot of current preventive health care

Abstract: Objective: To examine preventive health attendance and recording of type 2 diabetes and cardiovascular disease risk factors and their management in young Aboriginal peoples and Torres Strait Islanders (Indigenous Australians) at primary health care centres (PHCs). Methods:This descriptive cross-sectional study audited medical records of 1,986 Indigenous people aged 15-34 years attending 93 Australian PHCs. Measurements included blood pressure (BP), blood glucose level (BGL), smoking status, body mass index (BM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 29 publications
1
12
0
3
Order By: Relevance
“…Numbers of studies have shown that cardiovascular disease became the most common chronic disease with the progress of society and changes of people's life, which was an important burden of global public health in most countries [20][21][22]. Accumulating evidences suggested that endothelial dysfunction was one of the critical determinants in pathogenesis of atherosclerotic cardiovascular disease, and angiocardiopathy such as myocardial infarction, stroke, and vascular remodeling was independently associated with endothelial dysfunction [23][24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…Numbers of studies have shown that cardiovascular disease became the most common chronic disease with the progress of society and changes of people's life, which was an important burden of global public health in most countries [20][21][22]. Accumulating evidences suggested that endothelial dysfunction was one of the critical determinants in pathogenesis of atherosclerotic cardiovascular disease, and angiocardiopathy such as myocardial infarction, stroke, and vascular remodeling was independently associated with endothelial dysfunction [23][24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…However, the published literature on its effectiveness remains quite limited. We located 14 publications reporting on client care, [12][13][14][15][16][17][18][19][20][21][22][23][24][25] of which only 6 reported on client outcomes in the last 15 years. 14,15,18,19,21,22 Only three of these examined impacts across consecutive audits 14,22,23 and none reported on child health outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 4% of all women giving birth in Australia are Aboriginal and/or Torres Strait Islander (12,817 in 2014) [ 1 ]. While Aboriginal and Torres Strait Islander women tend to have babies at younger ages than non-Indigenous women [ 1 ], risk factors for non-communicable diseases (NCDs) are already common among young Aboriginal and Torres Strait Islander women [ 2 ]. Smoking, high-risk alcohol use, obesity, underweight, poor nutrition and gestational diabetes are risk factors for both adverse pregnancy outcomes and NCDs that are more common among Aboriginal and Torres Strait Islander women than non-Indigenous women [ 1 , 3 – 7 ].…”
Section: Introductionmentioning
confidence: 99%